Complexation of 4-Dimethylamino benzilidene(N-benzoyl)glycyl Hydrazone with Ni2+, Cu2+ and Cd2+ Ions and their Potentiometric Studies in Aqueous-Dioxane and Aqueous-Micellar Media - Promila Devi, Th.; Lonibala, R.K. (Asian Journal of Chemistry, 2010)
4-Dimethylamino benzilidene (N-benzoyl) glycyl hydrazone (HL) was prepared by the condensation of 4-dimethylamino benzaldehyde with N-benzoyl glycine hydrazide. Ni(II), Cu(II) and Cd(II) complexes of HL were synthesized and characterized based on the elemental analysis, conductivity, magnetic and spectral data. Protonation constant of the hydrazone and formation constants of the complexes have been determined potentiometrically at ionic strength 0.1 M KNO3 at different temperatures 17, 27 and 37 ºC in aqueous-dioxane and aqueous-micellar media. A single inflection in the potentiometric titration curves of the ligand indicates the presence of only one dissociable proton in the ligand. pH-metric and elemental analysis data show that the ligand forms only 1:1 metal-ligand complexes with Ni2+, Cu2+ and Cd2+ ions. The presence of the anionic and non-ionic surfactants in the medium decreases the protonation constant of HL and formation constant of the complexes. This is due to the compartmentalization of the reacting species between the bulk water and the micellar pseudophase. Thermodynamic parameters such as changes in free energy (DG), entropy (DS) and enthalpy (DH) associated with protonation of HL and formation of M(II)-HL complexes in different media are calculated and discussed.